Sosialisasi Gaya Hidup Bersih Dan Sehat Dengan Tema Manfaat Cuci Tangan Pakai Sabun (CTPS) Untuk Mencegah Penyakit ISPA Dan Diare - Abdurrahman Ridho; Andriani Putri; Ana Elvia Jakfar; Cut Mutia; Hayatun Maghfirah; Murhaban; Cukri Rahmi Niani (CV. Multi Kreasi Media, 2026)
Maintaining personal hygiene is a crucial step for individuals to prevent disease and achieve optimal health. Hygiene efforts should cover various body parts, particularly the hands, which frequently serve as mediators for spreading germs that cause diarrhea and Acute Respiratory Infections (ARI). A survey conducted at the Suci Hati Orphanage revealed that the children’s understanding of Handwashing with Soap (HWWS) remains low. Consequently, this community service initiative was implemented to socialize proper handwashing techniques. The objective is to foster awareness and healthy habits among the children to minimize the risk of disease transmission.